Faktor Lingkungan yang Berhubungan dengan Perilaku Buang Air Besar Sembarangan (BABS) di Wilayah Kerja Puskesmas Pujer Bondowoso - Aryadita, Natalia Rizki; Ningrum, Prehatin Trirahayu; Ririanty, Mury (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Unhygienic behavior and inadequate sanitation are still important problems for Indonesian citizens, especially in cases of open defecation. This study aims to analyze environmental factors related to open defecation behavior in Pujer District. This research was an observational analytic study with a cross-sectional design, involving 97 respondents selected by simple random sampling technique. Data collection was carried out by interviews and observations then analyzed descriptively, and continued with the Chi-square test. The results showed that there was a relationship between knowledge (p=0.013), attitude (p=0.000), ownership of a healthy latrine (p=0.000), availability of public toilets (p=0.005), availability of land (p=0.000), distance from house to river (p=0.004), the role of health workers (p=0.002) and support from village officials (p=0.020) with open defecation behavior. However, there was no relationship between age (p=0.105), availability of clean water (p=0.323) and soil conditions (p=0.371) with open defecation behavior. It is hoped that the puskesmas and health workers can increase the intensity of counseling and put up posters related to healthy latrines. Village officials are also expected to be able to give a warning if they see people defecating in an open manner.Keywords: environment; behavior; open defecation ABSTRAK Perilaku tidak higienis serta sanitasi yang kurang memadai masih menjadi persoalan penting bagi warga Indonesia khususnya pada kasus buang air besar sembarangan. Penelitian ini bertujuan untuk menganalisis faktor lingkungan yang berhubungan dengan perilaku buang air besar sembarangan di Kecamatan Pujer. Penelitian ini merupakan penelitian analitik observasional dengan rancangan cross-sectional, yang melibatkan 97 responden yang dipilih dengan teknik  simple random sampling. Pengumpulan data dilakukan dengan wawancara dan observasi kemudian dianalisis secara deskriptif, dan dilanjutkan dengan uji Chi-square. Hasil penelitian menunjukkan terdapat hubungan antara pengetahuan (p=0,013), sikap (p=0,000), kepemilikan jamban sehat (p=0,000), ketersediaan WC umum (p=0,005), ketersediaan lahan (p=0,000), jarak rumah ke sungai (p=0,004), peran petugas kesehatan (p=0,002) dan dukungan perangkat desa (p=0,020) dengan perilaku buang air besar sembarangan. Namun tidak terdapat hubungan antara umur (p=0,105), ketersediaan air bersih (p=0,323) dan kondisi tanah (p=0,371) dengan perilaku BABS. Pihak puskesmas dan tenaga kesehatan diharapkan dapat menambah intensitas penyuluhan serta melakukan pemasangan poster terkait jamban sehat, perangkat desa juga diharapkan dapat memberi teguran apabila melihat masyarakat buang air besar sembarangan.Kata kunci: lingkungan; perilaku; buang air besar sembarangan